1960
DOI: 10.1021/j100839a508
|View full text |Cite
|
Sign up to set email alerts
|

On the Oxidation of Gold

Abstract: I. Hydrogen exchange at 150°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1964
1964
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the surface of gold single crystals cannot be populated with chemisorbed molecular or dissociated oxygen, no matter how large the exposure to molecular oxygen (79,95), except at very high temperatures as described in Comsa's work (45)(46)(47)(48)(49). Although some early research reported chemisorption of oxygen (96)(97)(98), later work has ascribed these results to oxygen dissociation on calcium or silicon impurities (99,100). This has led researchers to employ other means to deliver oxygen to the surface.…”
Section: 2mentioning
confidence: 99%
“…However, the surface of gold single crystals cannot be populated with chemisorbed molecular or dissociated oxygen, no matter how large the exposure to molecular oxygen (79,95), except at very high temperatures as described in Comsa's work (45)(46)(47)(48)(49). Although some early research reported chemisorption of oxygen (96)(97)(98), later work has ascribed these results to oxygen dissociation on calcium or silicon impurities (99,100). This has led researchers to employ other means to deliver oxygen to the surface.…”
Section: 2mentioning
confidence: 99%
“…There have been many efforts over the years to investigate the interaction of oxygen with gold surfaces to better understand the unique oxidative catalytic properties of gold catalysts. Gold single-crystal surfaces do not measurably chemisorb oxygen either molecularly or dissociatively under ultrahigh vacuum (UHV) conditions or at elevated temperatures and pressures; , however, molecular oxygen physically adsorbs up to ∼50 K (physisorbed oxygen cannot be transferred to a chemisorbed state by simply annealing the surface). , Although some earlier investigations reported chemisorption of molecular oxygen on gold surfaces, researchers presented evidence later showing that the observed oxygen dissociation was actually induced by calcium , or silicon impurities.…”
Section: Adsorption Of Molecules/atoms On Au Single-crystalline Surfacesmentioning
confidence: 99%
“…The stable adsorption of 0.6 monolayer in dry air may be due to a film of gold oxide [17]. In the wet atmospheres, however, adsorption may have been on a water film on the gold.…”
Section: Figure 2 Adsorption Of Radiostearic Acid Onto Iron Filmsmentioning
confidence: 99%